DESIGN AND DEVELOPMENT OF MULTIMEDIA ANIMATION OF ROD MATERIALS DEFLECTION IN THE TOPICOF MATERIALS STRENGTH - Saputra, Nisa Aulia; Permana, Enda; Rohendi, Dedi (Journal of Mechanical Engineering Education, 2020)
Student centered learning is the effective learning that can make learners develop. In order to conducteffective student center learning, media isimportancein the learning process.Mediacan create interesting, interactive learning, and students can learn independently. Research on media development is very important, whichcreate a media that able to support student centered learning. This study aims to produce multimedia animation and to determine students’responses ofthe application of multimedia onthe topic of material strength inthe concept of deflection. "ADDIE" (Analysis, Design, Development, Implementation, Evaluation)were adapted in this research. Research subjects of this implementation of media are 30 students in the Department of Mechanical Engineering Education who have passedmaterial strength courses. Media experts and material experts in the Department of Mechanical Engineering Education carriedout judgment of the media. The results showsthat the produced multimedia are feasible with reference to the rating scale by experts with 92% of ratings by media experts and 86%from material experts. Students gave good responses to the media and in about 86% ofstudents interestedin the produced multimedia